PROGRAMMING OF GRAPHICAL INTERFACE IN APP DESIGNER OF MATLAB TO REPRESENT THE FOURIER SERIES IN INTRODUCTORY TELECOMMUNICATIONS COURSE - HUAMANÍ NAVARRETE, Pedro (2023)
This article describes the procedure for the implementation of a graphical user interface using the App Designer development environment of the Matlab software and its Toolbox Signal Processing and Symbolic Math, which allowed obtaining the Fourier Series coefficients for seven periodic signals followed by a graphical representation in the domain of time and frequency through pulses. Likewise, this  interface was implemented using various components such as Drop Down, Button, Knob, Axes, among others, which allowed the choice of the number of sinusoidal components used in the decomposition, as well as the choice of the type of signal, its amplitude, frequency, DC level and duration time of the same. Therefore, this implementation complements the teaching-learning process developed remotely for a topic in the Telecommunications I course of the 6th academic semester of the Electronic Engineering Degree at Ricardo Palma University. Finally, the graphical results are presented for the case of four choices of periodic signals, with different amplitudes, frequencies and DC levels; as well as the numerical results in terms of the mean square error, showing a lower value for the triangular signal despite using a reduced number of sinusoidal components